Epigallocatechin-3-gallate counters cisplatin toxicity of rat testes - Amr A. Fouad; Hatem O. Qutub; Abo Elyazied A. Fouad; Ahmed M. Audeh; Walid N. Al-Melhim (Taylor & Francis Group, 2017)
Context: Epigallocatechin-3-gallate (EG), the main active flavonoid in green tea, has well-known anti-inflammatory, antioxidant, and anti-apoptotic activities. Objective: The EG protection against testicular injury induced by cisplatin was studied in Sprague-Dawley rats. Materials and methods: Cisplatin (10 mg/kg, i.p) was given as a single injection to rats. EG was given at 40 and 80 mg/kg/day, i.p., for 5 days, starting the same day of cisplatin insult. Serum testosterone, and testicular malondialdehyde, total antioxidant status, nitric oxide, interleukin-6, interleukin-1β, cytochrome C, Bax/Bcl-2 ratio, and caspase-3 were measured. In addition, testicular histopathological examination and immunohistochemical expression of testicular tumour necrosis factor-α were evaluated. Results: Cisplatin, compared to the control, significantly decreased serum testosterone (6.48 ± 0.7 vs. 50.8 ± 4.91 ng/10 mL), and testicular tissue antioxidant status (17.3 ± 1.21 vs. 64.12 ± 5.4 μmol/g), and significantly increased interleukin-6 (85.81 ± 6.11 vs. 38.2 ± 2.79 pg/100 mg), interleukin-1β (98.09 ± 8.31 vs. 32.52 ± 2.08 pg/100 mg), malondialdehyde (74.5 ± 5.88 vs. 23.8 ± 1.91 nmol/g), nitric oxide (104.98 ± 8.5 vs. 52.68 ± 5.12 nmol/100 mg), cytochrome C (5.97 ± 0.33 vs. 1.6 ± 0.99 ng/mg protein), Bax/Bcl-2 ratio (4.01 ± 0.38 vs. 0.71 ± 0.0), and caspase-3 (3.2 ± 0.21 vs. 0.98 ± 0.08 O.D. 405 nm) in rat testes. EG (40 and 80 mg/kg, respectively) caused significant increases of serum testosterone (33.9 ± 2.89 and 47.88 ± 4.4 ng/10 mL), and testicular antioxidant status (47.1 ± 3.92 and 58.22 ± 3.58 μmol/g), and significant decreases of interleukin-6 (57.39 ± 4.2 and 48.18 ± 3.98 pg/100 mg), interleukin-1β (65.12 ± 5.88 and 41.96 ± 3.51 pg/100 mg), malondialdehyde (42.3 ± 3.9 and 28.67 ± 2.49 nmol/g), nitric oxide (70.6 ± 6.79 and 61.31 ± 5.18 nmol/100 mg), cytochrome C (3.4 ± 0.27 and 2.21 ± 0.18 ng/mg protein), Bax/Bcl-2 ratio (1.49 ± 0.14 and 1.1 ± 0.09), and caspase-3 (2.1 ± 0.17 and 1.48 ± 0.13 O.D. 405 nm) in testes of cisplatin-treated rats. Additionally, both doses of EG significantly ameliorated the histopathological injury and reduced tumour necrosis factor-α expression in rat testes. Conclusion: EG can afford testicular protection in cisplatin-challenged rats by its antioxidant, antinitrative, anti-inflammatory and antiapoptotic effects.